Impact of Low Hemoglobin on Contrast-Induced Nephropathy After Percutaneous Coronary Intervention (Cardiovascular Journal, 2012)
Background: Contrast-Induced Nephropathy (CIN) is an iatrogenic disorder, resulting from exposure to contrast media. The aim of this study was to assess whether anaemia is a predictor of contrast induced nephropathy after Percutaneous Coronary Intervention (PCI). Methods: This was a prospective observational study. A total of one hundred patients fulfilling the inclusion and exclusion criteria who underwent (PCI) Percutaneous Transluminal Coronary Angioplasty with stenting, were studied during the study period of two years from January 2008 to December 2009. Patients were divided into two groups : Group-I (n=50), patients with low hemoglobin (male 0.5 mg/dl from baseline) was used the incidence of CIN was 26% in low hemoglobin group and 8% in the normal hemoglobin group. Conclusion: preprocedural low hemoglobin is an independent determinant of increased incidence of contrast induced nephropathy after percutaneous coronary intervention. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12226 Cardiovasc. j. 2012; 5(1): 30-36